The usage of professionalisms in the language of fiction (in the examples of poet Tilewbergen Jumamuratov’s works) - Erjanovna, Seytnazarova Injayım (International Journal of Psychosocial Rehabilitation, 2020)
In the article it’s discussed about the professionalisms which are considered to be the limited lexical units of language, which are of great importance in all aspects of the development of the national literary written language and their usage in fiction language. The peculiarities of the usage of professionalism in the language of fiction are discovered in the works of the famous master of the Karakalpak nation T. Jumamuratov. Also, in the article the professionalisms used in the writer’s works are learned by separating into thematic groups. Some professionalism which don’t have common feature are analyzed, the meaning of them are told. However, there is also discuss about the stylistic services of the professional lexicon used in poetry as a means of various stylistic devices of the language.